Assessing kidney development and disease using kidney organoids and CRISPR engineering - Safi, Wajima; Marco, Andrés; Moya, Daniel; Prado, Patricia; Garreta, Elena; Montserrat, Nuria (Frontiers in Cell and Developmental Biology, 2022)
The differentiation of human pluripotent stem cells (hPSCs) towards organoids is one of the biggest scientific advances in regenerative medicine. Kidney organoids have not only laid the groundwork for various organ-like tissue systems but also provided insights into kidney embryonic development. Thus, several protocols for the differentiation of renal progenitors or mature cell types have been established. Insights into the interplay of developmental pathways in nephrogenesis and determination of different cell fates have enabled the in vitro recapitulation of nephrogenesis. Here we first provide an overview of kidney morphogenesis and patterning in the mouse model in order to dissect signalling pathways that are key to define culture conditions sustaining renal differentiation from hPSCs. Secondly, we also highlight how genome editing approaches have provided insights on the specific role of different genes and molecular pathways during renal differentiation from hPSCs. Based on this knowledge we further review how CRISPR/Cas9 technology has enabled the recapitulation and correction of cellular phenotypes associated with human renal disease. Last, we also revise how the field has positively benefited from emerging technologies as single cell RNA sequencing and discuss current limitations on kidney organoid technology that will take advantage from bioengineering solutions to help standardizing the use of this model systems to study kidney development and disease.